Digital privacy stressors and psychological adaptation: An environmental psychology study of high-income consumer well-being - Jijin Yang; Haliyana Khalid; Xiaoli Xu; Youyu Xu (Environment and Social Psychology, 2025)
Background: Digital service environments create unprecedented psychological stressors for individuals navigating privacy-personalization dilemmas, with affluent consumers experiencing heightened environmental anxiety due to intensive algorithmic targeting and surveillance pressures. High-income individuals exhibit unique psychological vulnerability patterns within digital contexts due to their elevated awareness of data manipulation mechanisms and intensified concern for identity protection, requiring specialized understanding of their stress-adaptation processes within technologically mediated environments. Purpose: This study examines how privacy-related environmental stressors trigger psychological adaptation mechanisms among affluent consumers, exploring the cognitive and emotional processes through which individuals manage privacy anxiety while maintaining psychological well-being in personalized digital service contexts. Methods: A quantitative approach was employed using stratified random sampling across luxury goods, financial services, and premium automotive sectors in four major Chinese cities. Data were collected from 468 valid responses from customers with annual consumption exceeding 100,000 RMB. Structural equation modeling analysis was conducted using SPSS 28.0 and Amos 26.0. Results: Good levels of model fit were obtained for all hypotheses. Psychological adaptation mechanisms were shown to significantly mediate the relationship between environmental stress factors and mental health outcomes (56.7%). Conclusions: Environmental stressors function as multi-dimensional constructs and of these, perceived environmental control is the more potent in affecting psychological adaptation. The study not only had applied theoretical integration between environmental stress theory and psychological adaptation frameworks but also offered practical implications for mental health professionals to construct differentiated treatment strategies for high income population.